Rekonstruksi Tematik atas Konsep Nabi dan Misi Kenabian dalam Alquran - Hasyim, Muh. Fathoni (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2019)
One of the very basic idea of the Qur’an is on the humanity of the prophet as like other creatures. Every single person has their own creative potency (in potentia) which, according to some philosophers, enables them to reach the degree of prophecy. This idea has then made a prophecy to come to a mundane term which has not to do with any sacred property. Prophets and prophecy are then not considered as an essential thing in human history. This notion has clearly put aside the role and function of prophet in human life. There is also popular opinion in the society that the prophet is considered as God’s chosen people to receive revelation, but, at some degree, they are conceived as having no responsibility to proselytize people under God’s revelation. This notion, beside to releases the prophet’s role from his social responsibility, contains some logical fallacies. If guiding people to the right path is being an individual’s responsibility of the follower of monotheist religion, how it is possible, then, to remove the responsibility of the prophets toward their society. Therefore, this study aims to revisiting the concept of prophecy, and analyzing the prophetic mission in terms of thematic interpretation